Analisis Studi Penelitian Tindakan Kelas (PTK): Efektivitas Model Pembelajaran Inkuiri terhadap Kemampuan Pemecahan Masalah pada Mahasiswa S1 Pendidikan Biologi - Kawuwung, Femmy Roosje; Mamahit, Jimmi Andrew (Jurnal Penelitian Pendidikan IPA, 2023)
The ability to solve problems is a skill that students should have in the 21st century to support better life activities. Observations on learning activities found that students were still relatively passive in learning activities, lacked confidence in conveying ideas, lacked the motivation to learn, and had no more interaction between students during learning, which affected low problem-solving abilities. It is in line with the evidence obtained through the acquisition of pre-research data where the results of problem-solving abilities include indicators of understanding problems with an average score of 55.63, indicators of preparing a settlement plan with an average value of 43.78, indicators of implementing a settlement plan with an average value of 50.37, and the indicator checks back with an average value of 46.53. Low problem-solving abilities can impact the quality of life of students who are less able to compete for jobs in the future. Increasing student solving needs to be considered so that from these problems, it is necessary to conduct classroom action research using the inquiry learning model to improve student problem-solving abilities, where this model has learning steps in guiding students to study in a directed manner and be able to solve problems. The research sample was 21 undergraduate students in Biology Education program. They obtained data through student activity questionnaires, student responses to learning models, model teacher activity questionnaires, and the results of problem-solving skills through giving test questions in the form of essays. This classroom action research was conducted in 3 learning cycles, with an average score between cycle I of 45.96%, cycle II of 94.78%, and cycle III of 95.26%. The acquisition of the average value shows an increase in problem-solving results between cycles I and II, cycles I and III. Testing the effectiveness of the learning model was carried out by the N-Gain test of 86.63% with the interpretation of "effective," and the distribution of the N-Gain score of 0.86 was greater than g > 0.7 with the "high" category. Obtaining these data can be concluded that the inquiry learning model effectively improves students' problem-solving abilities.